Identificación de plagas forestales insectiles en cinco localidades de la región San Martín - Díaz Ríos, Katiusca (2009)
This research was carried out in five localities of the San Martin Region (Rioja, Moyobamba, Las Palmas, Picota Juanjui) in each of these locations the sampling areas were different sites of production or processing. A Sawmill in the town of Rioja was surveyed for the implementation of this thesis. In the town of Moyobamba, a natural forest was considered as the sample area. In Las Palmas town, we considered as a sampling area, a sawmill, a forest plantation and a wild forest. In the town of Picota, the sampling was a sawmill. In the town of Juanjui we considered as a sampling area two sawmills and a forestry plantation. The field phase lasted approximately 8 months beginning in September 2007. The work consisted of sampling at each the places mentioned above. The samples were done randomly twice for each place or area. We did not use any type of statistical design. The objective of this work was to create a record of different ests in each locality and their hosts. The results are related to the presence of several pests that can be found at sawmills, forest plantations and forest which vary according to type of product to cause harm. This research also gives data of different hosts and different pests in each area or place where we do the sampling.